China Marine - Sledge, E. B. (Book collections on Project MUSE., 2002)
After Japan's surrender in 1945, Sledge and his company were sent to China to maintain order and to calm the seething cauldron of political and ideological unrest created by opposing factions. His regiment was the first Marine unit to return to the ancient city of Peiping (now Beijing) where they witnessed the last of old China and the rise of the Communist state.